PENGARUH JENIS LUKA PERINEUM TERHADAP WAKTU PENYEMBUHAN LUKA PERINEUM: Effect of Perineal Wound Type with Perineal Wound Healing Time - Layla Imroatu Zulaikha; Emi Yunita (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2022)
Complications of labor can occur from the first stage to the fourth stage, the presence of complications during labor can cause complications. One of the complications during labor that usually occurs is perineal laceration. The 2018 Indonesian Health Profile shows data that post partum infection cases reach a percentage of 80-90% due to lacerations during the delivery process. The method used in this research is correlation with cross sectional approach and analyzed by statistical test of contingency coefficient. The results of the study concluded that mothers who experienced perineal tears due to episiotomy were almost entirely faster in wound healing time, namely 88.25%, while mothers who experienced spontaneous perineal tears had a longer wound healing time, which was 66.67%. The results of the statistical test of the Contingency Coefficient using the SPSS 18 for windows program so that the value of = 0.05, df = 2, X2count = 12.20, X2table = 5.991. Because X2count > X2table, it can be concluded that H0 is rejected and H1 is accepted, which means that there is an effect of the type of perineal wound on the healing time of the wound. To overcome the above problems, early detection is carried out through routine ANC examinations so that the history of previous deliveries, estimated fetal weight, activity patterns and the mother's psychological condition can be known.